Comparative study on the responses of broiler chicken to hot and humid environment supplemented with different dietary levels and sources of selenium. (February 2020) - Dukare, Sagar; Mir, Nasir Akbar; Mandal, A.B.; Dev, Kapil; Begum, Jubeda; Tyagi, Praveen K.; Rokade, J.J.; Biswas, Avishek; Tyagi, Pramod K.; Bhanja, S.K.
Abstract: Present study was carried out with the objective of investigating the role of green synthesized nano Se (GNS) in growth performance, digestibility of minerals, immunity, stress alleviation, antioxidant status, and body Se content of broiler chicken raised under hot and humid environment with respect to market nano Se (MNS) and inorganic Se. The experimental design was 3 × 3 factorial, in which three levels (0.15, 0.20, and 0.25 ppm) and three sources (inorganic, green nano, and market nano) of Se resulted in nine treatments viz . IS-0.15, GNS-0.15, MNS-0.15, IZ-0.20, GNS-0.20, MNS-0.20, IS-0.25, GNS-0.25, and MNS-0.25 (IS: inorganic Se, GNS: green nano Se, MNS: market nano Se). A total of 432 broiler chicken were divided among nine treatments with six replicates of birds per treatment (8 birds/replicate). Results of present study revealed significantly better growth performance of birds supplemented with 0.25 ppm nano Se. The supplementation of 0.25 ppm nano Se improved the immune response and lymphoid organ development of birds. Significantly higher Se and nitrogen digestibility coefficients, serum antioxidant activity and decline of Heterophil: Lymphocyte ratio and expression of HSP70 gene were observed in birds supplemented with 0.25 ppm Se and nano source of Se compared to inorganic Se. Significantly higher Se concentration in liver and breast muscle and higher serum Se concentration were observed in birds fed 0.25 ppm nano Se. The liver Se concentration was much higher than that of breast muscle. However, the nano Se synthesized by green method in this study did not differ significantly from the chemically synthesized nano Se. It was concluded that 0.25 ppm Se and nano form of Se are superior to lower levels and inorganic form of Se, respectively, in improving the immunity, growth, antioxidant status, and in stress alleviation of broiler chicken. However, GNS is equally efficient as chemically synthesized MNS. Highlights: 0.25 ppm nano Se improves immunity & performance of broiler chicken under heat stress. 0.25 ppm nano Se improves antioxidant status & alleviates negative effects of heat stress in chicken. Green synthesized nano Se is equally efficient as chemically synthesized nano Se as poultry feed supplement. The eco-friendly green nano Se can be used in place of chemically synthesized nano Se.